2008
DOI: 10.2478/v10023-008-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

The Eastern Enlargement of the European Union: Challenges to Democracy?1

Abstract: Recent scholarship assesses the impact of the European Union's conditionality on democracy in Central and Eastern Europe in a contradictory way. On one hand, the EU is perceived as a key agent of successful democratic consolidation and on other hand, the return of nationalist and populist politics in new member states has been explored in the context of the negative consequences of the hasty accession that undermined government accountability and constrained public debate over policy alternatives. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…According to the Treaty on European Union, in this sense the EU uses the instruments of the normative power to put demands on countries to take steps for democratic reforms, while its main tools are creating incentives such as economic benefits or promises to be a member of the EU. The EU used democracy reforms as a condition in making its enlargement decisions in Eastern Europe (Malová & Dolný, 2008). The constructivist theory of international relations highlights the role of norms in promoting normative change in international relations by shaping the choices and acts that constitute a political order and rejecting realist assumptions regarding norms' effects.…”
Section: Democracy Promotion Is a Normative Processmentioning
confidence: 99%
“…According to the Treaty on European Union, in this sense the EU uses the instruments of the normative power to put demands on countries to take steps for democratic reforms, while its main tools are creating incentives such as economic benefits or promises to be a member of the EU. The EU used democracy reforms as a condition in making its enlargement decisions in Eastern Europe (Malová & Dolný, 2008). The constructivist theory of international relations highlights the role of norms in promoting normative change in international relations by shaping the choices and acts that constitute a political order and rejecting realist assumptions regarding norms' effects.…”
Section: Democracy Promotion Is a Normative Processmentioning
confidence: 99%
“…Popular sovereignty was, therefore, sacrificed in the name of pluralism and institutionalism; the process of democratisation visibly leaned towards the liberal tradition of democracy. Popular control and government accountability became limited mainly to elections (Malová and Dolný, 2011). As parliaments played a little role, the political debate became useless and political parties conformed to similar ‘centrist’ positions while anti-system parties were excluded.…”
Section: Political and Cultural Displacementsmentioning
confidence: 99%
“…In relation to the rule of law, they found that the 'instrumentalization of reforms' by local empowered yet unaccountable elites may lead to an abuse and politicization of newly created state structures, especially when the EU measures progress in outcomes rather than the processes of reforms (Mendelski 2016). In relation to social dialogue, Grosse (2010) and Malová and Dolný (2008) also hold that the EU accession process had a contradictory impact in Central and Eastern European countries. While the EU aimed at promoting the involvement of civil society in policy making, the technocratic character of the enlargement process achieved the opposite.…”
Section: Understanding the Impact Of Normative Dissonance: The Discip...mentioning
confidence: 99%